Plant extracts: Initial screening, identification of bioactive compounds and effect against Candida albicans biofilms - Lourenção Brighenti, Fernanda [UNESP]; Salvador, Marcos José; Gontijo, Aline Vidal Lacerda; Delbem, Alberto Carlos Botazzo [UNESP]; Delbem, Ádina Cléia Botazzo [UNESP]; Soares, Cristina Pacheco; De Oliveira, Maria Alcionéia Carvalho [UNESP]; Girondi, Camila Miorelli [UNESP]; Koga-Ito, Cristiane Yumi [UNESP] (Taylor & Francis, 2017)
Aim: This study screened plants from Brazilian Pantanal for Candida albicans antibiofilm activity. Material & Methods: Sixty extracts were obtained from ten plants using different extraction methods. Antifungal activity was assessed. Effects on biofilm inhibition and disruption and cytotoxicity were also evaluated. The most active extract was chemically characterized. Results: Buchenavia tomentosa ethanolic extract showed noticeable antifungal activity and was selected for biofilm experiments. Subinhibitory concentration of extract inhibited fungal adhesion. Maximum killing reached 90% of C. albicans cells in suspension and 65% of cells in biofilms. The active extract was noncytotoxic. Chemical characterization showed the presence of phenols. Ellagic and gallic acids showed activity on C. albicans. Conclusion: B. tomentosa extract and its isolated compound, ellagic acid, presented antibiofilm activity and low toxicity.
Keywords: antifungal agents; bioactive compounds; biofilms; Candida albicans